Gambaran Angka Prevalensi Mikrofilaria di Kabupaten Banyuasin Pasca Pengobatan Massal Tahap III - Reni Oktarina; Santoso Santoso; Yulian Taviv (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Filariasis is a chronic infectious disease that can cause permanent disability. One effort to interrupt transmission of filariasis is the Mass Drug Administration filariasis (MDA filariasis) in endemic areas of filariasis for 5 years. In 2012, MDA filariasis was carried out in all regions of Banyuasin. After treatment the 3rd year, it is necessary to evaluate the prevalence of microfilaria and microfilaria density. This activity was conducted by finger blood survey to people who’s living in sentinel and spot villages. This study selected 930 people for SDJ activities The test results obtained 4 positive of microfilaria Brugia malayi. The prevalence or microfilaria rate (Mf rate) in the village of sentinel was 0,96 with microfilaria density were 938/mL of blood, Mf rate in spot village was 0.31 with a microfilaria density were 217.75/mL of blood, while the Mf rate district was 0.43 with a microfilaria density were 716.06/mL of blood. People who suffer filiariasis mostly are farmers/fishermen. The prevalence of microfilariae in Banyuasin decreased, but the risk of transmission can still occur because of the density of microfilariae found> 50/mL of blood.